2013
DOI: 10.14483/23448350.4023
|View full text |Cite
|
Sign up to set email alerts
|

Dificultades De Comprensión De Nociones Relativas A La Clasificación Periódica De Los Elementos Químicos: La Opinión De Profesores E Investigadores En Educación Química

Abstract: ResumenEn este artículo se analizan las dificultades de aprendizaje de los alumnos de educación secundaria en torno al tema de la clasificación periódica de los elementos. Para ello, se recogen las opiniones de una muestra de profesores de Química y de didáctica de las ciencias obtenidas a partir de cuestionarios escritos y entrevistas individuales semiestructuradas. La información resultante es analizada a partir de un conjunto de ocho dimensiones, correspondientes a diferentes razones que pueden obstaculizar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
(8 reference statements)
1
8
0
1
Order By: Relevance
“…Another common difficulty concerns some atomic properties such as the atomic volume and electron configuration. A previous study 14,15 carried out by ourselves, in conjunction with Spanish experts in science education, revealed that the learning difficulties often encountered by high school students on this topic could be characterized into seven categories:…”
Section: ■ Periodic Table Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another common difficulty concerns some atomic properties such as the atomic volume and electron configuration. A previous study 14,15 carried out by ourselves, in conjunction with Spanish experts in science education, revealed that the learning difficulties often encountered by high school students on this topic could be characterized into seven categories:…”
Section: ■ Periodic Table Teachingmentioning
confidence: 99%
“…Furthermore, the games are resources that serve as contentrelated learning goals. Indeed, the games have been developed to create a climate of participation, involvement, and motivation for the students in an effort to help overcome the view that the PT is an arid and complicated issue 14 as precieved from a transmissive teaching approach.…”
Section: Purpose Of the Investigationmentioning
confidence: 99%
“…The first of these areas concerns the idea of an element as a chemical substance (Furió & Domínguez, 2001Raviolo, Garritz & Sosa, 2011) and, in turn, the distinction between elements and compounds (Briggs & Holding, 1986;Franco-Mariscal & Oliva-Martínez, 2012, 2013. Within this profile of learning problems, one must consider the work of Linares (2004), who described how one of the main difficulties with the concept of chemical elements lies in the ambiguous and ambivalent nature of this term.…”
Section: Difficulties Encountered In Learning About the Chemical Elemmentioning
confidence: 99%
“…As a consequence, with some exceptions (Ben-Zvi & Gemut, 1998;Franco-Mariscal, 2011;Linares, 2004;Taber, 1999;Taber & Tan, 2007;Talanquer, 2006Talanquer, , 2010Wang & Barrow, 2013), this can be considered to be an area in which very few research studies have been carried out. This situation exists despite the importance of this topic in introductory chemistry courses at the high school and university levels (Scerri, 2007) and despite the fact that students often struggle to learn and understand this topic, indicating that the various obstacles to learning should be analysed and clarified (Franco-Mariscal & Oliva-Martínez, 2012;Schmidt, 1998). As a result, it is of interest to define these shortcomings in teaching/learning and to identify strategies and resources that can contribute to overcoming them.…”
Section: Introductionmentioning
confidence: 99%
“…La enseñanza de la tabla periódica supone para el estudiante una dificultad asociada a la necesidad de memorizar el nombre de los elementos y símbolos químicos, por lo que le resulta también difícil clasificarlos, conocer cuáles tienen propiedades similares (Candia, 2016). Otra dificultad que se detecta está relacionada con la necesidad de abstracción para formarse un concepto acerca de la gran cantidad de elementos de la tabla periódica (Franco & Oliva, 2012). Como menciona Piaget (1984) se puede hacer abstracción de los objetos, lo que implicaría el contacto con los mismos o de la experiencia en interactuación con el fenómeno estudiado.…”
Section: Introductionunclassified